2013
DOI: 10.1186/1471-2474-14-57
|View full text |Cite
|
Sign up to set email alerts
|

Promoting work ability in a structured national rehabilitation program in patients with musculoskeletal disorders: outcomes and predictors in a prospective cohort study

Abstract: BackgroundMusculoskeletal disorders (MSDs) are a major reason for impaired work productivity and sick leave. In 2009, a national rehabilitation program was introduced in Sweden to promote work ability, and patients with MSDs were offered multimodal rehabilitation. The aim of this study was to analyse the effect of this program on health related quality of life, function, sick leave and work ability.MethodsWe conducted a prospective, observational cohort study including 406 patients with MSDs attending multimod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 37 publications
0
18
0
Order By: Relevance
“…The EQ-5D was applied to measure HRQoL because it has been found to have good prediction of return to work and the cut-off ≥0.6 on EQ-5D has been proposed to be a limit for having sufficient capacity to work for patients with BP and NP 39. Another cut-off has been used in a study of patients with musculoskeletal pain taking part in a national rehabilitation programme in Sweden where ≥0.5 on EQ-5D at start showed reduced sick leave days after the rehabilitation 53. Our population had a median EQ-5D score of 0.80, which is just below the mean scores for a Swedish normal population (0.84) 54.…”
Section: Resultsmentioning
confidence: 99%
“…The EQ-5D was applied to measure HRQoL because it has been found to have good prediction of return to work and the cut-off ≥0.6 on EQ-5D has been proposed to be a limit for having sufficient capacity to work for patients with BP and NP 39. Another cut-off has been used in a study of patients with musculoskeletal pain taking part in a national rehabilitation programme in Sweden where ≥0.5 on EQ-5D at start showed reduced sick leave days after the rehabilitation 53. Our population had a median EQ-5D score of 0.80, which is just below the mean scores for a Swedish normal population (0.84) 54.…”
Section: Resultsmentioning
confidence: 99%
“…Prolonging work participation reflects an important contribution to fulfilling societal roles. It has been suggested that becoming permanently work-disabled is associated with a poorer quality of life in general [ 13 - 15 ]. Since patients who experience at-work productivity loss are prone to develop sick leave and permanent work disability in the future, we hypothesize that at-work productivity loss is associated with a low quality of life.…”
Section: Introductionmentioning
confidence: 99%
“…To a large extent, it is related to the people of pre-retirement and retirement age was associated with the occurrence of musculoskeletal diseases and pain. In fact, musculoskeletal disorders are the main reason for reduced work efficiency and sick leaves in many developed countries [20]. Musculoskeletal diseases occur in younger and older employees, but in the latter group they cause a significant reduction in work ability over time [21].…”
Section: Discussionmentioning
confidence: 99%